PEMERIKSAAN TEKANAN DARAH, ASAM URAT DAN PENGETAHUAN TENTANG HIPERTENSI DI DESA TAMAN AYU KECAMATAN GERUNG KABUPATEN LOMBOK BARAT - Herlinawati, Herlinawati; Rahadianti, Dian; Sabariah, Sabariah; S. H., Diani; Adyana, I G. Angga (Nusantara Hasana Journal, 2022)
This community service is entitled "Blood Pressure Check, Uric Acid And Knowledge About Hypertension In Taman Ayu Village, Gerung District, West Lombok Regency". The method used in this activity is to check blood pressure, uric acid, blood sugar and cholesterol free of charge. Because Taman Ayu Village consists of 10 hamlets, so we asked each hamlet for 7-8 people. Participants were gathered at the Taman Ayu Village Office, where each participant's hamlet came in turn. Participants were asked to fill out informed consent, then they were examined, filled out questionnaires and intervened with education using booklet media. The implementation of community service activities which include checking blood pressure, uric acid and providing knowledge about hypertension went smoothly even though there were some elderly who came late, as well as when explaining, they had to repeat often considering that the service participants were the elderly. Support was also obtained from various sectors as evidenced by the large number of elderly who came during the activity and the location was facilitated by the Head of Taman Ayu Kematan Gerung Village, West Lombok.